2009
DOI: 10.1097/psy.0b013e318187c035
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Detection of Risk for Emotion Provoked Myocardial Ischemia

Abstract: Objectives-To test an easily administered, noninvasive technology to identify vulnerability to mental stress ischemia.Background-Myocardial ischemia provoked by emotional stress (MSI) in patients with stable coronary artery disease (CAD) predicts major adverse cardiac events. A clinically useful tool to risk stratify patients on this factor is not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 30 publications
2
27
0
Order By: Relevance
“…In previous research 15 , the peripheral vascular response to emotional stress was better able to predict a myocardial perfusion defect during this stress among patients taking vs not taking angiotensin converting enzyme (ACE) inhibitors, with 90% accuracy in predicting the patients who did not demonstrate this flow defect. Following upon this finding, Ramadan et al 16 examined whether ACE inhibition “protected” patients from a myocardial perfusion defect during mental stress.…”
Section: Recent Findingsmentioning
confidence: 97%
See 2 more Smart Citations
“…In previous research 15 , the peripheral vascular response to emotional stress was better able to predict a myocardial perfusion defect during this stress among patients taking vs not taking angiotensin converting enzyme (ACE) inhibitors, with 90% accuracy in predicting the patients who did not demonstrate this flow defect. Following upon this finding, Ramadan et al 16 examined whether ACE inhibition “protected” patients from a myocardial perfusion defect during mental stress.…”
Section: Recent Findingsmentioning
confidence: 97%
“…Psychological factors were also a focus of the REMIT Trial, including depression, which has repeatedly been strongly linked to recurrent-ACS and mortality risk 1415 . Boyle et al 13 reported that in REMIT, depression assessed by the Beck Depression Inventory (BDI) version II - but not the Centers for Disease Control Depression Scale - was marginally associated with probability of MSI, after adjustments for age, sex, resting LVEF, and resting wall motion (p = .053).…”
Section: Recent Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Laboratory studies have demonstrated that mental stress-induced myocardial ischemia occurs via several unique mechanisms, with the most consistently reported one seeming to be a widespread peripheral systemic vasoconstriction with consequent rapid rise in systemic vascular resistance and myocardial supply-demand related ischemia (6). In this issue of the journal, Burg and colleagues (7) demonstrate that this peripheral vasoconstrictive response to psychological stress provides a unique opportunity for the detection of mental stress ischemia. They report the utility of a novel peripheral arterial tonometry (PAT) technique for the detection of mental stress ischemia.…”
mentioning
confidence: 97%
“…Peripheral tonometric approaches have been developed for assessment of endothelial function and vascular health, and thresholds have been identified that provide acceptable sensitivity and specificity for myocardial ischemia. 31 The utilization of these technologies could be considered for the high risk, depressed, and diabetic patient group. Additional data to be included in risk stratification for the depressed patient with diabetes prior to MPI with mental stress could include thresholds of inflammation, ET-1, and body mass index, each of which has been implicated in the ischemia provoked under these conditions.…”
Section: Moving Forwardmentioning
confidence: 99%